UNUSUAL PRESENTATION OF ABDOMINAL TUBERCULOSIS - Ahmed, Elbashir Gusm Elbari; Magzoub, Mamoun; Elbushra, Sayed Mustafa (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 2 (2009), 2009)
Abdominal tuberculosis is not uncommon; Mycobacterium tuberculosis is either swallowed after coughing or in raw milk. Any site along the gastrointestinal tract may be infected. The 45 years –old, Sudanese male presented with abdominal wall sinuses, diarrhoea and weight loss. A clinical diagnosis of unusual abdominal tuberculosis was made and showed remarkable response to anti-tuberculosis therapy we would like to draw attention to unusual presentation of tuberculosis in areas where tuberculosis is common.